PENGENALAN BASSIC ENGLISH VOCABULARIES WITH PICTURES MEDIA KEPADA SISWA KELAS V SDN 137/III KOTO SALAK - Hermi Zaswita (XXXXX, 2022)
Abstract Based on observations of students in class V SD No. 137/III Koto Salak, teaching English is not a must, only as a local content and not all elementary schools make English as mulok. Some include Iqra' subjects, regional culture and skills as local content (mulok). So that there are educational institutions in elementary schools that provide English lessons but not a few do not. Even if given, the activities carried out are singing in English, not in the form of two-way conversations. For that, we need a forum that can provide alternative problem solving, namely the existence of free English learning activities, but not ignoring the quality of the results and the beauty of the process. In planning this media, the lecturer provides the media, then the media is used in teaching English vocabulary. The results of this service indicate that the use of Pictures Media is very helpful in the process of introducing vocabulary and the occurrence of real communication processes between teachers and students. Learning activities that seem to play make students not burdened with the material being taught, even students' motivation increases because of the reward hunting activity on the toys island. Keywords:  Vocabularies, Pictures Media, Elementary School, Learning